The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1063/1.3238505
|View full text |Cite
|
Sign up to set email alerts
|

Confocal single molecule fluorescence spectroscopy in ultrahigh vacuum

Abstract: We have constructed an ultrahigh vacuum confocal fluorescence microscope with the purpose of performing single molecule spectroscopy under highly defined conditions. The microscope is designed for high stability while affording the capability of sample preparation, sample transfer, and optical detection in ultrahigh vacuum. It achieves near-diffraction-limited performance and allows the observation of single molecule fluorescence dynamics over extended periods of time. The design of the microscope is discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Under this assumption, the emission from a SM will conform to two intensities, one for emission from the optically prepared state and another when the molecule populates a nonemissive state. However, recent applications of sophisticated algorithms such as change-point detection (CPD) in the analysis of SM emission have shown that multiple intensity states are present. Why would a SM demonstrate more than a single emission intensity? One explanation is spectral diffusion, environmental fluctuations of the ground-excited state energy gap altering the photoexcitation rate, and subsequently the emission intensity .…”
Section: Introductionmentioning
confidence: 99%
“…Under this assumption, the emission from a SM will conform to two intensities, one for emission from the optically prepared state and another when the molecule populates a nonemissive state. However, recent applications of sophisticated algorithms such as change-point detection (CPD) in the analysis of SM emission have shown that multiple intensity states are present. Why would a SM demonstrate more than a single emission intensity? One explanation is spectral diffusion, environmental fluctuations of the ground-excited state energy gap altering the photoexcitation rate, and subsequently the emission intensity .…”
Section: Introductionmentioning
confidence: 99%
“…As the operation of optoelectronic devices requires the application of electric fields (EF), the influence of EF on exciton dynamics in conjugated polymers is of great interest [5]. To better understand the interaction between the EF and organic photonic materials on the molecular level, single-molecule spectroscopy (SMS) is often used, which provides insights into some complex fluctuation phenomena that cannot be observed using standard ensemble techniques [6][7][8].…”
Section: Introductionmentioning
confidence: 99%